Food plants and landscapes: Use and conservation in Sertão do Ubatumirim, Ubatuba, Brazil - Rosa Macedo, Gabriela Silva Santa; Ming, Lin Chau [UNESP] (Universidade Federal do Paraná, 2019)
The management of food plants by traditional communities is crucial for biodiversity conservation, especially in locations where the unique biota has a high level of endemism. There are many factors responsible for changes on the local landscape during the years of 1966 to 2011. We discuss how protected areas (Picinguaba Nucleus of the Serra do Mar State Park and Bocaina National Park) and the traditional smallholder farmers' (caiçaras) management affected this scenario. We assume that continuous and in situ use of food plants are key factors for maintaining local biodiversity and we point out other drivers acting on this socioecological system, which is analyzed on this research. We collected data through participant observation, questionnaires and interviews. We used geoprocessing tools for linking landscape distinction emic criteria with phytosociological aspects, forest cover and diversity. These factors indicate that caiçara farmers should have a voice in decisions related to biodiversity conservation in both parks.
Plantas alimentícias e paisagens: Uso e conservação no Sertão do Ubatumirim, Ubatuba, Brasil
Keywords: Caiçara; Food plant management; Forest cover; Protected area